2022
DOI: 10.3390/cells11142170
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of Circulating Cell-Free HPV DNA in Plasma from Cervical Cancer Patients

Abstract: Circulating cell-free HPV DNA (ccfHPV DNA) may serve as a marker for cervical cancer. In this study, we used digital droplet PCR (ddPCR) to detect and quantify ccfHPV DNA in plasma from patients with HPV16- or HPV18-associated cervical cancer. Blood samples from 60 patients diagnosed with cervical cancer (FIGO IA1-IVA) at Aarhus or Odense University Hospital (June 2018 to March 2020) were collected prior to treatment, and patients were subdivided into an early stage (n = 30) and a late-stage subgroup (n = 30) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 59 publications
1
36
2
Order By: Relevance
“…[75][76][77] ctHPV DNA is more likely to have a larger role when CC is already diagnosed. While a few studies have shown that pretreatment ctHPV DNA levels do not correlate to prognosis, 54,56,57 several studies have demonstrated that persistent end-of-treatment ctHPV DNA seems to be a negative prognostic factor in cervical cancer 54,57 as well as in other HPV-related malignancies. 70,71 The most important clinical utility of ctHPV DNA in the future might however be as a surveillance marker for early detection of relapse and a few studies indicate that ctHPV DNA might be superior to clinical examination and radiology.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[75][76][77] ctHPV DNA is more likely to have a larger role when CC is already diagnosed. While a few studies have shown that pretreatment ctHPV DNA levels do not correlate to prognosis, 54,56,57 several studies have demonstrated that persistent end-of-treatment ctHPV DNA seems to be a negative prognostic factor in cervical cancer 54,57 as well as in other HPV-related malignancies. 70,71 The most important clinical utility of ctHPV DNA in the future might however be as a surveillance marker for early detection of relapse and a few studies indicate that ctHPV DNA might be superior to clinical examination and radiology.…”
Section: Discussionmentioning
confidence: 99%
“…55 Recently another two studies, stratifying between early-and advanced cervical cancer, found ctHPV DNA in the majority of advanced cases (94% and 63%, respectively), but in a minority of early-stage CC (26.7% and 10%, respectively). 56,57 T A B L E 1 Studies investigating detection of ctHPV DNA in pre-treatment liquid biopsies from patients with invasive cervical cancer 50,60 Of note, there was, surprisingly, rather poor correlation between HPV-status in plasma and in the cervix. 60 Thus, there are contradicting reports whether ctHPV DNA can be found in plasma from patients with precursor lesions.…”
Section: Cthpv Dna Detection In Cervical Carcinomasmentioning
confidence: 99%
See 3 more Smart Citations